Performance evaluation in healthcare buildings: a systematic literature review - Leitner, Drielle Sanchez; Santos, Adriana de Paula Lacerda (Ambiente Construído, 2022)
Healthcare buildings are complex as their occupants may have different health conditions. In this context, building performance evaluations can help to achieve better performance perceived by occupants. Thus, this paper has developed a systematic literature review (SLR) on performance evaluation in healthcare buildings to understand their intrinsic characteristics, in addition to developing an overview of the subject. The objective was to identify the purpose of the evaluations, the criteria evaluated, the evaluation methods, the type of healthcare facilities evaluated, as well as the temporal and spatial distribution of papers. The research was conducted using three electronic databases, and eighty-three papers were examined according to the 5W1H tool. As a result, the buildings assessed covered health services at all stages of life, physical and mental issues. Six groups of criteria were identified, highlighting: spatial, lighting, acoustic comfort, energy issues, and the materials and finishes used. Moreover, relationships were established between the types of buildings, evaluated criteria, and tools used. Finally, the SLR collaborated with the understanding of performance in healthcare buildings, identified that these buildings are being evaluated, contributing to the health, well-being, and satisfaction of occupants as buildings that perform better tend to be better places of healing and work.